Modelo de arranjo físico de armazém baseado em classificação de estoque de supermercado - Atamanczuk, Mauricio Joao (2009)
The present study proposed a methodology of stock classification and position of items in a warehouse layout for the supermarket sector. It exclusively approached the problem of storage and handling in warehouses. To do so, the rules of health surveillance were taken into consideration, as well as the operational peculiarities of this sector. The research was carried out by the experimental method. Data from a supermarket were used to carry out these tests with the proposed models. For the methodology of classification 24 groups of products which take into account the health demands for safe storage were defined. Some facilities in the process of storing were also considered, such as the distribution of beverages according to their packaging, and solid foods in block and shelf storing. The model proposed for the classification was based on a flowchart which has only binary decisions. The maximum of six questionings were done to determine the classification of a product in one of the groups. The answers, positive or negative ones, were given a code: 1 or 0, respectively. The junction of the binary codes generates an exclusive code for each group of products. The groups that present similar criteria and can be stored near each other were grouped in five storing classes. The designation of the spaces to be occupied by the items in the warehouse was done, firstly, for each class through a heuristic proposal. The spaces occupied by the classes were divided for the groups through the use of a linear program. The main contributions of the research refer to the storing of similar products which are near each other, and mainly, to the classification model of the stocks that respect the food safety rules, and also provides enough assistance for the making out of layouts adequate to supermarket warehouses.